The effect of early entrepreneurship education: Evidence from a randomized field experiment - Laura Rosendahl Huber; Randolph Sloof; Mirjam van Praag (Institute for the Study of Labor (IZA), 2012)
The aim of this study is to analyze the effectiveness of early entrepreneurship education. To this end, we conduct a randomized field experiment to evaluate a leading entrepreneurship education program that is taught worldwide in the final grade of primary school. We focus on pupils' development of relevant skill sets for entrepreneurial activity, both cognitive and non-cognitive. The results indicate that cognitive entrepreneurial skills are unaffected by the program. However, the program has a robust positive effect on non-cognitive entrepreneurial skills. This is surprising since previous evaluations found zero or negative effects. Because these earlier studies all pertain to education for adolescents, our result tentatively suggests that non-cognitive entrepreneurial skills are best developed at an early age.
urn:nbn:de:101:1-201208096305
Keywords: L26; I21; J24; C93; 330; skill formation; field experiment; entrepreneurship education; entrepreneurship; Gründungsausbildung; Unternehmer; Kognition; Feldforschung